2020
DOI: 10.1111/jpn.13313
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation regulates milk production variables, metabolic associated genes and pathways in perinatal Holsteins

Abstract: Perinatal period is the critical time in dairy cattle due to negative energy balance and high milk production stress. Being a key role in biosynthesis and methylation cycle, folic acid is considered essential for lactational and metabolic performance in dairy cattle. Thus, the current study was designed to evaluate the effect of folic acid supplementation on milk production phenotypic traits in periparturient cows. Transcriptomic screening was performed for milk production and metabolism‐associated differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…The inadequate supply of folic acid may lead to a DNA mismatch repair and abnormal cell growth because of the essential role in the synthesis of DNA. Similarly, in a recently published study, many essential genes, such as ALDOA, PKM, SDS, SDSL, ASS1, POLD3, XDH, and ARG1, in response to folic acid treatment, were documented as being significantly associated with the biosynthesis of amino acid signaling [58]. Moreover, MCM2, MCM3, POLD3, and LIG1 were documented to have an involvement in DNA replication and mismatch repair, while PHOSPHO1, LPCAT2, GPAT2, and GPAT3 were found to control the glycerophospholipid metabolism.…”
Section: Folic Acid Alone or In Combination With Vitamin B12 Improves Milk Production And Metabolism In Periparturient Dairy Cattlementioning
confidence: 57%
See 4 more Smart Citations
“…The inadequate supply of folic acid may lead to a DNA mismatch repair and abnormal cell growth because of the essential role in the synthesis of DNA. Similarly, in a recently published study, many essential genes, such as ALDOA, PKM, SDS, SDSL, ASS1, POLD3, XDH, and ARG1, in response to folic acid treatment, were documented as being significantly associated with the biosynthesis of amino acid signaling [58]. Moreover, MCM2, MCM3, POLD3, and LIG1 were documented to have an involvement in DNA replication and mismatch repair, while PHOSPHO1, LPCAT2, GPAT2, and GPAT3 were found to control the glycerophospholipid metabolism.…”
Section: Folic Acid Alone or In Combination With Vitamin B12 Improves Milk Production And Metabolism In Periparturient Dairy Cattlementioning
confidence: 57%
“…Pathways are important for sustaining homeostasis within an organism, and the flow of metabolites through a pathway is controlled based on the cell's needs and the substrate's availability. We also noted in our previously published study that the majority of genes demonstrated their importance for the mediation of metabolic signaling, which further speeds up various biological processes related to metabolism [58]. Folic acid acts in the acceptance and release of one-carbon units [27], which are vital for the biosynthesis of purine, pyrimidine, and DNA, and also offers the methyl group for the formation of S-adenosylmethionine.…”
Section: Folic Acid Alone or In Combination With Vitamin B12 Improves Milk Production And Metabolism In Periparturient Dairy Cattlementioning
confidence: 79%
See 3 more Smart Citations